PH Responsive Self-Assembly of Cucurbit[7]urils and Polystyrene-Block-Polyvinylpyridine Micelles for Hydrophobic Drug Delivery. (19th November 2013) - Moosa, Basem A.; Mashat, Afnan; Li, Wengang; Fhayli, Karim; Khashab, Niveen M.
Abstract : Polystyrene-block-polyvinylpyridine (PS-b-P4VP) polypseudorotaxanes with cucurbit[7]urils (CB[7]) were prepared from water soluble PS-b-P4VPH + polymer and CB[7] in aqueous solution at room temperature. At acidic and neutral pH, the pyridinium block of PS-b-P4VP is protonated (PS-b-P4VPH + ) pushing CB[7] to preferably host the P4VP block. At basic pH (pH 8), P4VP is not charged and thus is not able to strongly complex CB[7]. This phenomenon was verified further by monitoring the release of pyrene, a hydrophobic cargo model, from a PS-b-P4VPH + /CB[7] micellar membrane. Release study of UV active pyrene from the membrane at different pH values revealed that the system is only operational under basic conditions and that the host-guest interaction of CB[7] with P4VPH + significantly slows down cargo release.